2017
DOI: 10.1088/1757-899x/245/8/082015
|View full text |Cite
|
Sign up to set email alerts
|

Urban Heat Island Effect on the Energy Consumption of Institutional Buildings in Rome

Abstract: Abstract. The urban heat island (UHI) effect is constantly increasing the energy consumption of buildings, especially in summer periods. The energy gap between the estimated energy performance -often simulated without considering UHI -and the real operational consumption is especially relevant for institutional buildings, where the cooling needs are in general higher than in other kind of buildings, due to more internal gains (people, appliances) and different architectural design (more transparent façades and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These outcomes provide additional understanding of the varying findings from earlier studies, likely confounded by the different approaches used (e.g., Partial correlation analysis versus Pearson correlation). (6) The relationships between LST and landscape metrics could be affected by spatial autocorrelation. In general, the study highlighted that applying different statistical approaches, spatial scale, and abundance of UGS can appropriately determine the effectiveness of configuration metrics to predict the association between LST and UGS patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These outcomes provide additional understanding of the varying findings from earlier studies, likely confounded by the different approaches used (e.g., Partial correlation analysis versus Pearson correlation). (6) The relationships between LST and landscape metrics could be affected by spatial autocorrelation. In general, the study highlighted that applying different statistical approaches, spatial scale, and abundance of UGS can appropriately determine the effectiveness of configuration metrics to predict the association between LST and UGS patterns.…”
Section: Discussionmentioning
confidence: 99%
“…On the other end, urbanization has also been associated with environmental and ecological stresses [2][3][4]. One of the widely recorded and evident impacts associated with urbanization is the increased temperature over the cities relative to the adjacent rural areas, or the urban heat island (UHI) [5,6]. Relative to the rural regions, urban areas have distinct morphology, geometry, and infrastructure that contributes to the UHI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in UHIs also raises energy consumption due to more cooling needs, particularly during summers (Calice et al, 2017;Magli et al, 2015). Moreover, studies have reported how heat stress related morbidity and mortality soar with increasing UHI effect (Madrigano et al, 2015;Mohanaselvan & Bhaskar, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In Mediterranean climates, heating or cooling needs are predominant, depending on climatic specific location. In Rome, a little prevalence of heating need has been found (Calice et al 2017). However, climate change affects the energy requirements of buildings in a way that a shift between heating and cooling needs has to be expected in the near future (Jenkins et al 2009, Sailor 2014, Santamouris 2014, Toledo et al 2016.…”
Section: Introductionmentioning
confidence: 99%